(untitled) (Jurnal Teknologi (Sciences & Engineering), 2018)
The development of radar technology, Synthetic Aperture Radar (SAR), Circularly Polarized-Synthetic Aperture Radar (CP-SAR) and geostationary satellite, demanding needs of communication facilities and infrastructures that have variety platforms, which can generate processed data with high resolution and better image quality for all types of explored terrain. Owing to the antenna embedded on the body of geostationary satellite, its shape should be compact, small, and simple configuration, i.e. the equilateral triangle with and without truncated-tip c1, c2, c3, and c3s antennas using probe and microstrip-line feed with low-power at S-band (2.5 GHz - 2.9 GHz). The Method of Moments (MoM) is chosen in the numerical analysis for fast calculation. The performance results for c2 and c3 antennas are almost same, for instance the values of gain and axial ratio (Ar) for each antenna are consecutive of 6.8 dBic and 0.42 dB. Moreover, the performance results for c1, c3, and c3s antennas at the each resonant frequency are relatively different, as follows: c1 antenna operates at the frequency 2.76 GHz, gain RHCP = 6.66 dBic, Ar = 2.91 dB, the operation frequency of c3 antenna is 2.9 GHz, gain LHCP = 6.98 dBic, Ar = 3.02 dB, and for c3s antenna has the operation frequency of 2.5 GHz, gain LHCP = 6.08 dBic, Ar = 1.75 dB. The results for both simulation and measurement of equilateral triangle antenna, especially for Ar bandwidth below 3-dB are about 0.02 GHz and 0.015 GHz, respectively. Furthermore, the results of the 3 dB-Ar beamwidth for simulation and measurement in elevation plane consecutively are about 120Â° and 80Â°.